2014
DOI: 10.1017/pasa.2014.15
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cyg OB2 #11(O5 Ifc) by Modelling its Atmosphere

Abstract: We continue the study of O-supergiants belonging to the association Cyg OB2 using moderate-resolution spectra. In this paper we present results of the modelling of the stellar atmosphere of Cyg OB2 #11. This object belongs to the spectral class Ofc, which was recently introduced and is yet small in numbers. Ofc class consists of stars with normal spectra with CIII λλ4647, 4650, 4652 emission lines of comparable intensity to those of the Of-defining lines NIII λλ4634, 4640, 4642. We combined new spectral data o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Our analysis of nine most representative spectra, obtained between October 2002 and December 2014, when the star displayed an ample range of variation in visual luminosity, shows that the bolometric luminosity of GR 290 is variable, it is higher 1 Results was published in Maryeva et al (2013b) and Maryeva et al (2014) during the phases of greater optical brightness. It confirms the hypothesis from earlier works by Polcaro et al (2011) and Maryeva & Abolmasov (2012a).…”
Section: Romano's Starmentioning
confidence: 86%
“…Our analysis of nine most representative spectra, obtained between October 2002 and December 2014, when the star displayed an ample range of variation in visual luminosity, shows that the bolometric luminosity of GR 290 is variable, it is higher 1 Results was published in Maryeva et al (2013b) and Maryeva et al (2014) during the phases of greater optical brightness. It confirms the hypothesis from earlier works by Polcaro et al (2011) and Maryeva & Abolmasov (2012a).…”
Section: Romano's Starmentioning
confidence: 86%
“…Using double-lined eclipsing binaries Kiminki et al 2015 found that the distance is 1.33 kpc. In this work, as well as in previous studies (Maryeva et al 2013(Maryeva et al , 2014, we used an estimation of distance d=1.5 kpc from Mel'nik & Dambis (2009), who acquired it from the analysis of line-of-sight velocities and proper motions of OB-associations. Note that the uncertainty of distance of 0.1 kpc results in uncertainty of model stellar magnitude of about 0.14 mag, which is comparable to the errors of apparent stellar magnitudes.…”
Section: Determination Of Bolometric Luminosity and Mass Loss Ratementioning
confidence: 99%
“…Main works devoted to the numerical modelling of stellar atmospheres in Cyg OB2 association are Herrero et al (1999Herrero et al ( , 2002; Negueruela et al (2008). Moreover, individual supergiants were studied by Najarro et al (2011); Maryeva et al (2013Maryeva et al ( , 2014. * E-mail: olga.maryeva@gmail.com In the present work we model the stellar atmospheres of five stars initially assumed to have V luminosity class (dwarfs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation